A inserção da cultura indígena no currículo da escola na comunidade Canauanim: um instrumento de resistência cultural ou um novo instrumento de dominação cultural? - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
In recent years, there is increasing advocacy by indigenous peoples, to put the indigenous culture in the school curricula in communities. This has generated intense debates between the movement of indigenous teachers and governments, as well as the creation of specific legislation has generated conflict on official bodies dealing with indigenous education. Many indigenous schools, throughout these 25 years, have increasingly entered the indigenous culture in their curricula. Therefore, this study was conducted to analyze the process of inclusion of indigenous culture in the school curriculum of indigenous communities from 1988 to the present day. To analyze what was the impact of this process to Wapichana people, we developed a case study with a qualitative approach through archival and field research in the State Indigenous School Tuxaua Luiz Cadete, which is located in the Community of Canauanim, Serra da Lua region, Cantá town, in Roraima. That community has a population of 978 Indians, divided into 168 families, and the school has, according to the 2012 school census, 275 students, 20 teachers, 01 staff and 01 administrative area School Manager. So the research was conducted through semi-structured interviews with 15 people: 04 teachers, 05 students, 02 indigenous leaders, and responsible for 04 students. We also did direct observation during extra activities and events held by the school. Thus, we found that the inclusion of culture in the curriculum Wapichana State School Indigenous Tuxaua Luiz Cadete has served as an instrument of resistance to these people. Even with advances in educational public policy, there are still several clashes with the state due to lack of flexibility in administrative, educational, and regulatory frameworks of the State Education and Sports Secretary. In spite of many advances in relation to the curriculum and pedagogical practices adopted by teachers, there is no clarity on how to evaluate activities related to traditional elements of culture. Moreover, there is little motivation for students and their parents to be more involved in these activities and the construction of a curriculum that enables students to assert their identity and strengthen the corporate design Wapichana people.
Keywords: Política pública educacional; Cultura indígena wapichana; Currículo escolar; Educational public policy; Wapichana indigenous culture; School curriculum; CIÊNCIAS HUMANAS: ANTROPOLOGIA